Performance Evaluation of Combining with Medical and Old-Age Care in Pension Institutions of China: A Two-Stage Data Envelopment Analysis - Du N; Wu P; Yuan M; Li Z (Dove Medical Press, 2021)
Na Du,1 Peng Wu,2 Man Yuan,3 Zhiwu Li4 1Southern District of The Second Hospital of Shandong University, Jinan, People's Republic of China; 2School of Economics and Management, Fuzhou University, Fuzhou, People's Republic of China; 3The Third Affiliated Hospital of Soochow University, Changzhou, People's Republic of China; 4The Institute of Systems Engineering, Macau University of Science and Technology, Macau, People's Republic of ChinaCorrespondence: Man Yuan Email yuanm2290@163.comPurpose: The aim of this paper was to build a performance evaluation index system for the combination of medical and old-age care services in pension institutions of China.Methods: A two-stage data envelopment analysis (DEA) is used to evaluate the performance of 30 pension institutions in China.Results: The results show that the two-stage DEA accounted for a relatively high affiance of medical and nursing care services, but resource allocation still needs to be further optimized. Institutions with ineffective DEA need to reduce the five factors of operations, management, fixed assets, technology and services in the input dimension.Conclusion: In the output dimension, the service evaluation effect and safety management effect need to be improved. The performance of combined old-age care and medical care in old-age institutions can be improved in terms of investment in fixed assets, methods of capital subsidies, supervision and management, as well as standardized operations.Keywords: medical and old-age care service, performance evaluation, two-stage DEA